Tank combat the theory and practice of tank warfare 1916-2000 - Jörgensen, Christer 1967-; Mann, Chris (Historian) (Strategy and tactics, 2017)
Illustrated throughout with black-and-white action photographs, Tank Combat is a definitive guide to the art of armoured combat in the twentieth century